MENGUKUR KESUKSESAN IMPLEMENTASI SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI BALI DENGAN MODEL DELONE DAN MCLEAN - Lestara Permana, Gusi Putu; Cahyaning Putri, Ni Putu Eka (Universitas Prof.Hazairin,SH Bengkulu, 2022)
Through the use of Management Information Systems, the company has utilized technology to help improve service and business quality. The Management Information System used in the organization, for example at the Regional Office of the Ministry of Religion of the Province of Bali which uses a Management Information System as a tool for achieving goals based on the application they use. The Regional Office of the Ministry of Religion of Bali Province made the decision to use the Application from the Institutional Level Financial Application System (SAKTI) in January 2022. The results of this study suggest that, the four main constructs of Information Quality to users, System Quality to Users, System Quality to User Satisfaction, and Users to Net Benefits, were rejected based on test results which indicated that these constructs were not able to assess the successful implementation of the application. Institution Level Financial Application System (SAKTI). However, Information Quality on user satisfaction, Service Quality on users, Service Quality on User Satisfaction, Users on User Satisfaction and User Satisfaction with Net Benefits, of the 5 constructs were accepted based on test results which indicated that this construct was able to assess the success of the implementation of Application of the Institution Level Financial Application System (SAKTI) at the Regional Office of the Ministry of Religion of the Province of Bali.